Visas and walls: border security in the age of terrorism - Avdan, Nazli (De Gruyter E-Books Sozialwissenschaften, 2019)
Borders traditionally served to insulate nations from other states and to provide bulwarks against intrusion by foreign armies. In the age of terrorism, borders are more frequently perceived as protection against threats from determined individuals arriving from elsewhere. After a deadly terrorist attack, leaders immediately encounter pressure to close their borders. As Nazli Avdan observes, cracking down on border crossings and policing migration enhance security. However, the imperatives of globalization demand that borders remain open to legal travel and economic exchange. While stricter border policies may be symbolically valuable and pragmatically safer, according to Avdan, they are economically costly, restricting trade between neighbors and damaging commercial ties. In Visas and Walls, Avdan argues that the balance between economics and security is contingent on how close to home threats, whether actual or potential, originate. When terrorist events affect the residents of a country or take place within its borders, economic ties matter less. When terrorist violence strikes elsewhere and does not involve its citizens, the unaffected state's investment in globalization carries the day.Avdan examines the visa waiver programs and visa control policies of several countries in place in 2010, including Turkey's migration policies; analyzes the visa issuance practices of the European Union from 2003 until 2015; and explores how terrorism and trade affected states' propensities to build border walls in the post-World War II era. Her findings challenge the claim that border crackdowns are a reflexive response to terrorist violence and qualify globalists' assertions that economic globalization makes for open borders. Visas and Walls encourages policymakers and leaders to consider more broadly the effects of economic interdependence on policies governing borders and their permeability.